Learning Arabic writing skill at Ningxia University China: Analysis study - Nan, Ma Ruo; Suo Yan Mei (European Journal of Social Science Education and Research, 2020)
This research focuses on the analysis of the in Arabic writing skill at Ningxia University of China. The research focuses on two main questions: how do students are proficient in writing skill, and how can teachers have a good command of the skills of writing. The aim of this research is teaching and learning skill for writing in Arabic lessons. The researchers explained the reasons for error in writing to students. This research was based on the collection of information for world scholars and their theories. This research was used by observation and questionnaire for digital analysis, according to the observations of writing skill and by the data analysis, the researcher will benefit from the teaching and learning skill of writing in Arabic in this university. During the case of correct analytical study, the research followed the inductive approach, the descriptive approach and the analytical approach. This research was based on the inductive and descriptive approach for collecting information of the world scholars and their theories. The research analyzes the data to use analytical approach. The research sample consisted of 100 male and female students from this university. It collected 100 copies of the questionnaire for students. The researchers used the spss tool to perform the number analysis. At the end of the research results, in view of the fact that students specializing in Arabic obtained good results in the written tests conducted in this research. The researchers found that students tend to textbooks to acquire the skill of writing in Arabic.
Keywords: Learning. Arabic writing skill, Ningxia University China